Mathematical Knowledge for Teaching in Elementary Teacher Education: A Systematic Review with Limited Meta-Analytic Synthesis - Meita Fitrianawati; Muhammad Ardi Kurniawan; Vita Istihapsari (The Indonesian Institute of Science and Technology Research, 2026)
This study synthesizes empirical research on Mathematical Knowledge for Teaching (MKT) in elementary teacher education through a systematic review combined with a limited meta-analytic synthesis. Following PRISMA 2020 procedures, studies published between 2015 and 2025 were identified from ERIC, Scopus, Google Scholar, Garuda Kemdikbud, and DOAJ. Fourteen quantitative and mixed-methods studies met the inclusion criteria, although only five provided sufficient statistical data for effect size estimation. Effect sizes were calculated using Cohen’s d and Hedges’ g, and pooled under a random-effects model in CMA version 3 and the R-package metafor. The findings indicate that MKT among elementary teachers, both prospective and early-career, is generally uneven across domains, with stronger performance in common content knowledge and persistent weaknesses in specialized content knowledge and horizon content knowledge, especially in fractions and geometry. The pooled effect (d = 0.62, 95% CI [0.38, 0.86], k = 5) suggests that structured pedagogical interventions can improve MKT, although the evidence base remains limited and heterogeneous. Cross-study patterns, rather than formal subgroup meta-analytic tests, suggest that teaching experience, mathematical content domain, and initial pedagogical knowledge are associated with variation in MKT outcomes. The study highlights implications for strengthening elementary teacher education curricula, particularly within the Kurikulum Merdeka framework in Indonesia, and for improving future MKT research design and reporting.